Penggunaan Sistem Teknologi Digital untuk Kelancaran LogistikTugboat di PT. Kartika Samudra Adijaya - Hasnur , Juliandri; Putra, Riki Wanda; Fitri, Dayana (Jurnal Cakrawala Bahari, 2025)
The rapid development of digital technology has become a critical component in enhancing efficiency and precision within maritime logistics operations, particularly in tugboat activities. This research explores the challenges faced in utilizing digital technology systems that support the operational flow of tugboat logistics at PT. Kartika Samudra Adijaya. Employing a qualitative descriptive method, the study gathers data through interviews, document analysis, and field observations. The results highlight several major obstacles, including low levels of digital proficiency among employees, unstable internet connections, insufficient system integration, and irregularities in data entry and information management. Additionally, reluctance to adopt new technologies and inadequate system upkeep contribute to delays and reduced operational effectiveness. The study emphasizes that improving digital skills, strengthening technological infrastructure, and increasing system dependability are essential actions to maximize the use of digital technology in tugboat logistics. These efforts are expected to enhance operational continuity and improve overall logistics performance. Overall, the study emphasizes that the success of digital technology implementation in tugboat logistics does not solely depend on systems and devices, but also on workforce readiness, sufficient financial support.